Cultivation and Analysis of Citronella Essential Oil Compounds for Traditional Medicine Development - Dewa Ayu Ika Pramitha; Agung Ari Chandra Wibawa; Nyoman Budiartha Siada; Gde Nyoman Astika; Ni Made Sukma Sanjiwani (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This study addresses challenges faced by Mahapraja, a Bali tourist cottage. It explores issues related to citronella cultivation, trust-building, limited land, equipment underutilization, and marketing hurdles. It is relevant for regional traditional medicine and agriculture. Method: This research uses a mixed-method approach, combining qualitative data collection (interviews, surveys, observations) with quantitative analysis (Gas Chromatography-Mass Spectrophotometer). Pre- and post-tests gauge knowledge enhancement during socialization activities. Practical Applications: The findings improve citronella cultivation in Mahapraja, boosting essential oil production and benefiting the cottage and traditional medicine industry. It informs marketing strategies, instilling confidence in producing and selling derivative products. Conclusion: This study highlights Mahapraja's citronella challenges, setting the stage for agricultural improvements and effective marketing. It underscores research's role in advancing regional traditional medicine and agriculture, positioning Mahapraja for success in citronella essential oil production and sales.